TorakochirurgiaEarly and late results of concomitant lung cancer resection and off-pump CABG - Dyszkiewicz, Wojciech; Jemielity, Marek; Rogowski, Jan; Rzyman, Witold; Piwkowski, Cezary; Marjanski, Tomasz; Perek, Bartłomiej; Siondalski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Aim: The aim of this study was to present the early and late results of lung resection for cancer with simultaneous myocardial revascularization on the beating heart (OPCAB). Material and methods: From 2001 to 2006, 42 patients (33 men and 9 women, mean age 62 yrs) with resectable lung cancer and unstable angina were operated on. The majority of patients were classified as stage II of lung cancer (AJCC) and stage II of ischaemic heart disease (CCS). Twenty-four lobectomies, eleven pneumonectomies, six wedge resections and one bilobectomy were carried out together with aortocoronary graft implantation (mean: 1.9 graft per patient). OPCAB preceded the lung resections. Results: There were no postoperative deaths or perioperative myocardial infarctions. The most frequent complications were as follows: atrial fibrillation (15%), atelectasis and residual pneumothorax. Patients were followed up for 8 to 60 months. Within this period of time 17 patients died, mostly due to cancer relapse. Local recurrence of lung cancer and distant metastases were the only factors that statistically influenced late survival of patients. Probability of survival in patients without metastases was nearly 90%. Five-year follow-up did not reveal any patients with acute myocardial infarction. In 7 patients symptoms of recurrent angina occurred and in 3 of them coronary stents were placed. Conclusions: Lung resection carried out simultaneously with OPCAB is a safe and effective method for the treatment of both diseases – lung cancer and myocardial ischaemia. Concomitant lung resection and myocardial revascularization can be a good alternative for two-stage treatment in which cardiological interventions or cardiac surgery precede lung cancer resection. The late results in this group of patients are mostly affected by lung cancer recurrence.